Innovation structure combining inter-story isolation with passive cooling effect for AP1000 nuclear power plants. Issue 3 (29th September 2021) - Hou, Gangling; Liu, Yu; Wang, Tao; Wang, Binsheng; Song, Tianshu; Sun, Menghan; Li, Yong
Abstract : Purpose: An inter-story isolation structure (IIS) for AP1000 nuclear power plants (NPPs) is provided to resolve the conflict of seismic safety and the optimal location of air intakes. Design/methodology/approach: The effect of passive cooling system (PCS) is better with lower altitude of air intakes than that in the original design of AP1000 NPPs. Seismic performances of IIS NPPs, including the seismic responses, damping frequency bandwidth and seismic reduction robustness, are improved by combining the position of air intakes lower and the optimal design method. Findings: Theoretical analysis and numerical simulation are illustrated that the seismic reduction failure of IIS NPPs is the lowest probability of occurrence when PCS has highest working efficiency. Originality/value: The IIS NPPs can transfer the contradiction between PCS work efficiency and seismic safety of NPPs to the mutual promotion of them.